Quantification of cardiac subvolume dosimetry using a 17 segment model of the left ventricle in breast cancer patients receiving tangential beam radiotherapy. (March 2019) - Tang, Simon; Otton, James; Holloway, Lois; Delaney, Geoffrey P.; Liney, Gary; George, Armia; Jameson, Michael; Tran, David; Batumalai, Vikneswary; Thomas, Liza; Koh, Eng-Siew
Highlights: Novel contouring method delineating subvolumes of left ventricle is feasible. American Heart Association 17 segment model allows accurate description of radiation dose delivered. Correlation of mean heart dose to segmental doses range from weak to moderate. Segmental dose readings can be better paired with imaging detected cardiac abnormalities. Abstract: Purpose: Subacute changes following breast radiotherapy have been demonstrated in discrete areas of the left ventricle (LV), with recent guidelines being developed to help determine dose to subvolumes of the LV. This study aims to determine doses to the 17 segments of the LV as per the American Heart Association (AHA) and other cardiac subvolumes, and to correlate mean heart (MHD) dose with various subvolume dosimetric indices. These results may direct focus to specific left ventricular segments in studies of radiation-related heart disease incorporating surveillance imaging, help to determine more precise dose response relationships, and potentially aid prediction of late radiation effects. Methods and materials: The heart and cardiac subvolumes of 29 patients treated with tangential radiotherapy for left breast cancer were contoured. Delineation of cardiac subvolumes (cardiac chambers, cardiac valves and the 17 segments of the LV) was undertaken using a novel contouring method on planning CT data reformatted into the cardiac axis. Individual segments were then combined to determine doses to the basal, mid and apical left ventricular regions, and the anterior, septal, inferior and lateral ventricular walls. Radiotherapy doses (including maximum, mean, D1cc, V25) were determined. Correlation analyses were performed between MHD and various substructure dosimetric indices. Results: Twenty five patients received tangential breast free breathing radiotherapy alone, and four patients received regional nodal irradiation including the internal mammary chain with deep inspiration breath hold (DIBH). For patients receiving breast only radiation, the median mean heart radiation dose was 2.62 Gy (range 1.52–3.90 Gy), and a heterogeneous dose distribution to the LV was noted, with the apical region receiving the highest median mean dose (14.99 Gy) compared with the mid and basal regions (3.10 Gy and 1.51 Gy respectively). The anterior LV wall received the highest median mean dose (9.21 Gy) with the remaining walls receiving similar mean doses (range 1.79–3.05 Gy). The anterior LV apical segment (segment 13) and apex (segment 17) received the highest individual median mean segment doses (26.73 Gy and 30.02 Gy respectively). Apical segments received the highest median mean doses (segments 13, 14, 15, 16), followed by the mid anterior (segment 7) and anteroseptal (segment 8) segments. Segments receiving the highest doses remained unchanged between the DIBH cohort and free breathing cohort. MHD showed a high correlation with the anterior wall r  = 0.71, p  < 0.05 and entire left ventricle r  = 0.82, p  < 0.05, but correlations varied from weak to high when MHD was correlated with segments receiving highest doses (range r  = 0.43–0.76), p  < 0.05. Conclusions: In the setting of breast cancer radiotherapy, there are substantial RT dose variations within specific LV segments, with mid and apical anterior ventricular segments (segments 7, 13) and the apical region of the LV (segments 13, 14, 15, 16, 17) being consistently exposed to the highest radiation doses. Determining segmental and regional RT doses to the left ventricle may help guide focus in diagnostic cardiology in the post radiotherapy setting.